2013
DOI: 10.1007/s12639-013-0236-2
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis sp. from food animals in India

Abstract: Blastocystis, a zoonotic protozoan found in the intestinal tracts of a wide range of animals, has not been reported from non-human hosts from India so far. Organisms indistinguishable from Blastocystis sp. were identified in the Giemsa stained intestinal scrapings collected from carcasses of piglet and poultry that were brought for necropsy to the Central University Laboratory, Chennai.The 'central vacuole forms' of the parasite, with number of nuclei ranging from 1 to 12 were identified. The intensity of infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It slightly increased and significantly decreased after supplementation with B. subtilis strains 87Y and 67, respectively. Blastocystis is an opportunistic pathogen and has previously been shown to cause a wide range of gastrointestinal tract symptoms [ 51 ]. Importantly, the addition of fermented or unfermented rapeseed meal showed inhibition of protozoan B. hominis development.…”
Section: Discussionmentioning
confidence: 99%
“…It slightly increased and significantly decreased after supplementation with B. subtilis strains 87Y and 67, respectively. Blastocystis is an opportunistic pathogen and has previously been shown to cause a wide range of gastrointestinal tract symptoms [ 51 ]. Importantly, the addition of fermented or unfermented rapeseed meal showed inhibition of protozoan B. hominis development.…”
Section: Discussionmentioning
confidence: 99%
“…Conferring to the study of Zaki et al (1991), enduring smears seem to be the technique of choice for light microscopic analysis. The staining characteristic of Blastocystis with Giemsa is alike to that defined by Yamada & Yoshikawa (2012) and Sreekumar et al (2014) with the occurrence of an amorphous and granular substantial in the central vacuole and fluctuating number of nuclei (1-12) in the external rim of the cytoplasm. Morphological characteristics of Blastocystis in turkey isolates were observed.…”
Section: Discussionmentioning
confidence: 80%
“…in turkey population was moderate with the prevalence of 43.8% (70/160) concurrent with Blastocystis infection in turkey from Egypt with 50% (6/12) prevalence (Mokhtar & Youssef, 2018). However, Sreekumar et al (2014) reported high prevalence of infection in turkey from India with 70% (3/4).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To date, the overall infection rate of Blastocystis in chickens is 30.4% (1193/3, 927) globally and 20.1% (372/1, 854) in China according to previous studies and this study (Table 4). Of note, in most published studies with higher Blastocystis infection rates, chicken samples were collected from intensive poultry farms with high breeding densities, and lower Blastocystis infection rates were found in chickens kept in zoos (Deng et al., 2021; Lee & Stenzel, 1999; Sreekumar et al., 2014). However, the Hotan Black chickens sampled in this study underwent gross free‐range rearing.…”
Section: Discussionmentioning
confidence: 99%